Southern chronicles: The political ecology of class in the Italian industrial periphery - Pusceddu, A. M. (2024)
This article focuses on class as a central concept for analyzing the common ground of labor and environmental struggles. Through the examination of the frictions between industrial workers and environmentalists in Brindisi, an industrial city in the Italian South, the article unravels the socio-ecological dilemmas underlying their valuation frameworks. It addresses the job blackmail as a central element of the framework through which workers and environmentalists understand the contradictory forces at work in the local socio-ecological crisis. The article looks at the critical junctions that underpin the making of the local working class. As concrete determinations of capitalist socio-ecological contradictions, these junctions constitute the focus for the political ecology of class pursued in this article. To illuminate the place-bound experience of these contradictions, the article looks at the tension between value and values in shaping the experience of the work–environment nexus. Assuming the centrality of class for labor and environmental struggles, the article argues for the re-articulation of the fields of workers and environmentalists as a crucial step towards the definition of a common emancipatory socio-ecological project.